2013
DOI: 10.1007/s00228-013-1545-1
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analyses of dose-exposure relationships for gabapentin following oral administration of gabapentin and gabapentin enacarbil

Abstract: The meta-analyses addressed issues associated with between-study variability; and confirmed the highly non-linear nature of dose-exposure relationships for gabapentin and the essentially linear relationships for gabapentin enacarbil. The resulting models could be used to simulate exposure at any clinically relevant dose and bridge therapeutic dose range between the two drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…For example, the bioavailability of carbamazepine is considered to be 80% on average, but ranges considerably [72]. In the case of gabapentin, bioavailability is inversely proportional to the taken dose, resulting in reduced increases in exposure with increasing doses [73]. Finally, absorption and first-pass metabolism can be influenced by food intake and beverages, such as grapefruit juice [74].…”
Section: Drug-food Interaction and Formulation Variabilitymentioning
confidence: 99%
“…For example, the bioavailability of carbamazepine is considered to be 80% on average, but ranges considerably [72]. In the case of gabapentin, bioavailability is inversely proportional to the taken dose, resulting in reduced increases in exposure with increasing doses [73]. Finally, absorption and first-pass metabolism can be influenced by food intake and beverages, such as grapefruit juice [74].…”
Section: Drug-food Interaction and Formulation Variabilitymentioning
confidence: 99%
“…Gabapentin is removed from the plasma by hemodialysis, and thus, the drug is not recommended for patients with RLS receiving hemodialysis 28. Recently, a meta-analysis of dose–exposure relationships for gabapentin after oral administration of gabapentin and gabapentin enacarbil was reported 49. The study collected published pharmacokinetic data for gabapentin and gabapentin enacarbil from 35 identified studies conducted in at least 192–497 subjects.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…The AUC of gabapentin after a gabapentin enacarbil 700 mg dose (53.0 μg hour/mL) was also comparable to the gabapentin AUC (56.6 μg hour/mL) after a gabapentin dose of 1,200 mg/day, a standard antiepilepsy dose 69. A recent meta-analysis study of 35 pharmacokinetic studies on gabapentin and gabapentin enacarbil included an accurate conversion graph of the two drugs and suggested that the therapeutic effects of 900 to 1,800 mg of gabapentin were comparable to the same dose range of gabapentin enacarbil 49. If this is correct, one can apply the safety data of gabapentin to gabapentin enacarbil at least by 1,800 mg/day and confidently reduce the potential risk for pancreatic acinar cell tumor in patients treated with gabapentin enacarbil, similar to that with gabapentin.…”
Section: Benefit–risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioavailability of GBP is inversely proportional to the dose: 60% at 900 mg/day and 27% at 4800 mg/day (administered in three divided doses) [76] . In contrast, its prodrug, enacarbil, showed essentially linear dose-proportional pharmacokinetic properties [77,78] . GBP has a volume of distribution of 58 L after 150 mg intravenous administration [76] .…”
Section: Gabapentin (Gbp)mentioning
confidence: 99%